PSYCHOLOGY AND PERSONAL DEVELOPMENT: OVERCOMING STRESS (Ustozlar uchun, 2025)
This article highlights important aspects of psychology and personal development, analyzing issues such as overcoming stress, building self-confidence, resilience in the face of difficulties, and setting appropriate goals in a person’s life. It explains the causes of stress and presents simple yet practical methods for managing it effectively. The psychological foundations of self-confidence, the process of its formation, and its impact on human activity are also explored. The article substantiates the internal factors that enable some people not to give up when facing difficulties, as well as the importance of psychological stability. In addition, the difference between dreams and plans is clarified, emphasizing that setting clear goals is a key factor in personal success. This article is intended to be useful for young people and a broad audience interested in personal development.